2022
DOI: 10.1088/1742-6596/2253/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Firefly algorithm and ant colony algorithm to optimize the traveling salesman problem

Abstract: Through the study of ACOTSP, it is found that the previous ant colony algorithm will fall into local optimal when increasing pheromone concentration factor. In order to solve the problem, we through the improved pheromone concentration factor to view your traveling salesman solving process, through the simulation experiments found that due to the pheromone concentration gradually increased with the number of iterations, pheromone concentration and pheromone concentration factor exponential relationship, lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The path nodes constructed by the ant colon algorithm, as shown in Figure 2a, exhibit intersections, resulting in a path length o 7639. 31. By implementing local optimization, the cross-interference can be eliminated.…”
Section: Local Optimization Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The path nodes constructed by the ant colon algorithm, as shown in Figure 2a, exhibit intersections, resulting in a path length o 7639. 31. By implementing local optimization, the cross-interference can be eliminated.…”
Section: Local Optimization Strategymentioning
confidence: 99%
“…Shahadat et al [30] adopted the general formula of visibility heuristic associated with the final destination city to intelligently deal with the problem of returning to the starting city. Yu et al [31] found that the traditional ant colony algorithm would fall into the local optimum when increasing the pheromone concentration factor. To solve this problem, a disturbance factor was added to the algorithm to eliminate the interference of other factors on the ant colony movement, and then the functional relationship between the moving distance and the pheromone concentration was increased.…”
Section: Introductionmentioning
confidence: 99%
“…The research is based on static networks and considers the dynamic uncertainty of the scene less. In [ 12 ], the routing algorithm based on the Firefly algorithm to optimize FCM (Firefly algorithm to optimize fuzzy C-means, FFACM) establishes a cost function by calculating the link cost between nodes, which improves the energy consumption of nodes. In addition, the routing overhead can also be reduced by probabilistic broadcasting based on trust [ 13 ].…”
Section: Introductionmentioning
confidence: 99%